Study of a Space-Time Monitoring of High-Speed Railway Underline Structure Using Distributed Optical Vibration Sensing Technology - Baye Mbaye Diouf; Ailan Che; Shaokong Feng (Shock and Vibration)
The phenomenon of vibration is quite frequent in various engineering works. Vibration analysis and monitoring occupy a significant place in scientific measurements and engineering applications. The quality of the underline structure actively influences the response of high-speed railway track plate and trackside. Due to years of service and under the action of train loads, bond failure between supporting track plate and cement asphalt mortar layer will imminently occur. And this will significantly influence the vertical dynamic response of a track slab and severely affect the safe operation of the entire railway system which can subsequently lead to a risk of derailment. Firstly, the purpose of the present study is to develop a practical 2D dynamic interaction model of vehicle-track subgrade based on a two-step simulation capable of analyzing the dynamic response of a track slab under different fault distribution in the CA mortar layer by using the commercial software Abaqus. Secondly, the distributed optical vibration sensing (DOVS) technology is discussed and applied on a section of high-speed railway near the Hongqiao station which has been in operation after a long period of degradation for real-time vibration monitoring. Overall, the numerical simulation results show that, in the elastic field, the track plate defects have a significant amplification effect on the vibration, and the magnification can be more than 2 to 3 times. The vibration monitoring results reveal two elements of the fault effects on the track slab dynamic response: the amplification of the dynamic response when the train is arriving and leaving the monitoring section and also causing extreme resonance when the train is passing increasing the vibration signal largely.